2022
DOI: 10.1016/j.hpb.2021.08.939
|View full text |Cite
|
Sign up to set email alerts
|

Pan-European survey on the implementation of robotic and laparoscopic minimally invasive liver surgery

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
0
27
0
2
Order By: Relevance
“…Conversion rate to open decreased by 4.5% after 70 operations [ 61 ]. Zwart et al found a reduction in operative time and conversion to open after 55 operations and a second reduction point after 145 cases for conversion rate [ 62 ].…”
Section: Learning Curvementioning
confidence: 99%
See 1 more Smart Citation
“…Conversion rate to open decreased by 4.5% after 70 operations [ 61 ]. Zwart et al found a reduction in operative time and conversion to open after 55 operations and a second reduction point after 145 cases for conversion rate [ 62 ].…”
Section: Learning Curvementioning
confidence: 99%
“…Zwart et al showed, that the vessel sealer is the second most used device for parenchymal transection in an Pan-European survey including 120 surgeons in 24 countries [ 62 ].…”
Section: Technical and Surgical Aspectsmentioning
confidence: 99%
“…According to the updated Southampton guidelines, hepatic surgery should preferably be performed with a minimally invasive approach [ 1 , 25 , 26 , 27 , 28 , 29 ]. In this context, RALS was first reported by Giulianotti et al in 2003 and is gaining more and more popularity [ 17 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the last two decades, several papers have confirmed the feasibility of minimally invasive liver surgery (MILS) and shown the advantages of MILS over open liver resection, especially regarding hospital stay and postoperative morbidity (1)(2)(3)(4). However, the widespread use of MILS is not the reality yet, ranging from 10% in some countries (5) to up to 30% in others, depending on expertise, availability, and surgical volume (6).…”
Section: Laparoscopic and Robotic Liver Surgerymentioning
confidence: 99%
“…However, the widespread use of MILS is not the reality yet, ranging from 10% in some countries ( 5 ) to up to 30% in others, depending on expertise, availability, and surgical volume ( 6 ). A recent survey has shown that, even in highly specialized European centers, MILS comprised about one third of all liver resections ( 2 ). These numbers are expected to increase further in the near future, once MILS have been incorporated as part of the general training program, especially in the HPB fellowship program.…”
mentioning
confidence: 99%